Phonon Structure Engineering for Intrinsically Spectrally Selective Emitters by Anion Groups - Rui Zhang; Enhui Huang; Wenying Zhong; Bo Xu (Photonics)
Spectrally selective emitters (SSEs) have attracted considerable attention, because of radiative cooling, which could dissipate the heat from earth to outer space through the atmospheric window without any energy input. Intrinsically inorganic SSEs have significant advantages to other SSEs, such as the low fabrication cost due to the extremely simple structures and long life span under solar exposure. However, few inorganic materials can act as intrinsic SSEs due to the limited emissions in the atmospheric window. Here, we propose a strategy to design intrinsic SSEs by complementing the IR-active phonons in atmospheric window with anion groups. Accordingly, we demonstrate borates containing both [BO3]3− and [BO4]5− units can exhibit high emissivity within the whole atmospheric window, because the IR-active phonons of [BO3]3− units usually locate around 8 and 13 μm, while those of [BO4]5− units distribute in 9~11 μm. Furthermore, K3B6O10Cl and BaAlBO4 are selected as two examples to display their near-unity emissivity (>95%) within the whole atmospheric window experimentally. These results not only offer a new strategy for the design of intrinsic SSEs, but also endow wide band-gap borates containing both [BO3]3− and [BO4]5− units with great potential applications for radiative cooling.